Implementasi Data Mining Dalam Menentukan Penjualan Alat Perabot Dengan Menggunakan Metode K-Means Clustering Pada PT.XYZ - Silvia Lestari; Rahmatun Nazila; Lukna Aulia Ulhar; Muhammad Zidane (International Forum of Researchers and Lecturers, 2024)
The increasing development of technology and increasing buying and selling activities require every business owner to adapt to technological developments, for business owners selling or processing sales data is very important as is done by PT.XYZ household furniture items such as tables, chairs, dressers, wardrobes, sofas and many more, where sales data is still done manually, such as a lack of reviewing what products consumers need and ineffective data storage. To overcome this problem the researcher tried to implement it using one of the methods available in data mining, namely the K-Means Algorithm. –certain data groups (clusters). So, by grouping this data, the company can find out which items are selling best and which are not selling well. So that the goods in the warehouse do not pile up. From this research, the resulting output is 5 of the best-selling items, and 5 of the least-selling items. With the data processing carried out, it is hoped that it can provide solutions to the company so that they can find out which items are the best-selling and best-selling items.